The Power of the Weak: on Worthiness of Elders in Folk Culture - Kalniuk, Tomasz (Poznańskie Studia Slawistyczne, 2013)
The folk culture from the turn of the 20th century was founded on the mythical paradigm. Its specific feature was an opposition between the self and the other. It had ambivalent influence on those people and places which, due to actual or perceptual reasons, were placed on the margin of the mainstream of life. This includes, among others, the elders. On the one hand, they were treated by the community with reluctance, or even aggression, because of their decrepitude. On the other hand, they were respected as guards of traditions, and intermediaries with the supernatural, who possessed a portion of its potential.